Expression pattern of galectin-1 and galectin-3 in rat testes and epididymis during postnatal development - Özbek, Mehmet; Hitit, Mustafa; Yıldırım, Nuh; Özgenç, Özge; Ergün, Emel; Ergün, Levent; Beyaz, Feyzullah; Kurtdede, Nevin; Altunay, Hikmet (Elsevier BV, 2018)
Galectins are a family of lectins-binding beta-galactosides involved in a variety of extracellular and intracellular processes, thereby contributing to homeostasis, cell adhesion, cellular turnover, and immunity. This study aimed to determine the localization and expression of galectin-1 (Gal-1) and galectin-3 (Gal-3) in the testis and epididymis of rats at postnatal [(prepubertal (day 5), pubertal (day 20), postpubertal (day 50) and mature (day 70)] periods by using immunohistochemistry and Western blotting. Gal-1 and Gal-3 were differentially expressed in different types of cells in the testis and epididymis during postnatal development. While we detected Gal-1 expression in some spermatogenic cells and Leydig cells in the testis, not in the epididymal epithelium, Gal-3 was expressed in Sertoli cells, peritubular myoid cells, Leydig cells, smooth muscles and interstitial CD68-positive macrophages. Epithelial cells of the corpus and cauda epididymis showed an intense Gal-3 expression. Gal-1 expression was higher in the testis than in the epididymis on days 50 and 70. The expression of Gal-3 in the testis increased from the prepubertal to mature period. While the expression difference of Gal-3 was not statistically significant in the testis and epididymis until puberty, Gal-3 expression in the postpubertal and mature periods was higher in the epididymis. The expression of Gal-3 in the corpus and cauda epididymis was higher than that in the caput epididymis. In conclusion, our findings suggest that puberty has potential regulatory effect on the expression of galectins in testis and epididymis of rats. Gal-1 and 3 may play a role in the development of the reproductive system and the preservation of the immune-privileged environment in the testis, due to their pro-apoptotic and anti-apoptotic functions. The presence of intense expression of Gal-3 in the corpus and cauda epididymis may contribute to the maturation and storage of spermatozoa.
Keywords: Epididymis; Male; Galectin 1; Galectin 3; Galectins; Blotting, Western; Blood Proteins; Immunohistochemistry; Rats; Testis; Animals; 3. Good health